ADOPTION OF SCIENTIFIC LIVESTOCK MANAGEMENT PRACTICES BY TRIBAL AND NON-TRIBAL FARM WOMEN (Indian Journal of Animal Production and Management, 2013)
dairy animal management practices followed by the tribal and non tribal farm women in Chittorgarh district of southern Rajasthan. The results of the analysis revealed that technology adoption level of non-tribal farm women with respect to breeding, feeding, housing, milking and healthcare and hygiene practices of dairy animals is quite higher side than tribal farm women. The finding could be helpful to extension worker and policy makers to formulate more effective mechanism for transmitting the technological information to the end users, so that farm women can optimally utilise the technologies for improving the productivity of their livestock.
Keywords: Tribal; Non-tribal; farm women; dairy husbandry; MPS; adoption